(untitled) (Homoeopathy for All, 2024)
World Food Day is celebrated on October 16th every year to commemorate the founding of the United Nations’ Food and Agriculture Organization (FAO) in 1945. The day aims to raise awareness about global hunger, food security, and the importance of healthy and sustainable food systems. It focuses on the eradication of hunger, promoting nutritious food for all, and addressing global food related challenges, such as food waste, malnutrition, and climate change. While homeopathy primarily deals with individual health conditions through natural remedies, there can be some indirect links between World Food Day’s themes and homeopathy: